Influence of organizational culture and organizational commitment to the effectiveness of control systems internal government and it’s impact on the quality of financial statements - Lenny Dermawan Sembiring; Juan Anastasia Putri; Ruth Tridianti Sianipar; Hery Silitonga (Enrichment : Journal of Management, 2023)
This research aims to discover, test and analyze the influence of organizational culture and organizational commitment of the effectiveness of efectiviveness goverment internal control and its impact on the quality of financial statement either partially or simultaneous. The research method used is the analysis of quantitative data. The object of this research is local government in the province of North Sumatra. Sampling method is purposive sampling. The technique of data collection was done through the distribution of questionnaires. While the techniques of data analysis is path analysis and the data is processed using SPSS statistics software. The results showed that in organizational culture influences the effectiveness of government internal control systems, organizational commitment influences the effectiveness of government internal control systems, organizational culture and organizational commitment simultaneously influences the effectiveness of government internal control systems, organizational culture influences the quality of financial statements, organizational commitment does not affect the quality of reports finance, effectiveness of government internal control systems affect the quality of financial statements, organizational culture, organizational commitment and effectiveness of government internal control systems affect the quality of financial statements, and organizational culture and organizational commitment through the effectiveness of government internal control systems affect the quality of financial statements.